Sustainable governance indicators 2019 Turkey report - GENÇKAYA, ÖMER FARUK (Bertelsmann Stiftung, 2019)
The period under review was marked by ongoing deep political and social divisions in Turkey. The failed coup attempt of 15 July 2016 and the subsequent state of emergency (which lasted almost two years) enabled a major constitutional referendum, which led to the political system changing from a parliamentary to a presidential governance model. The government’s politically charged allegations, judicial investigations and dismissal of thousands of civil servants, and the immense organizational capacity of the Gülenist movement in the public and private sector brought public trust to rock-bottom levels. Rising popular authoritarianism has undermined the rule of law, legal certainty and judicial independence, exacerbated widespread social discrimination, and reinforced the presidential model and exclusion of the legislature from government processes. Following the June 2018 early parliamentary and presidential elections, the governmental system was changed to a presidential model and the Prime Minister’s Office was abolished. The organization of the new presidential system was regulated by presidential decree in July 2018. Currently there are 16 line ministries and nine policy councils, which develop the government’s long-term strategy and report on government progress. The Ministry of Development, which was the primary consultation body for preparing policies according to the government’s program, was abolished. In addition, four offices were established: finance, investment, digital transformation and human resources. The war in Syria has had a profound impact on Turkish politics and society. The government’s extensive military counterinsurgency in predominantly Kurdish provinces in the southeast of Turkey and the military intervention in northern Syria have brought the peace process between the Turkish state and PKK to an end. The government appears to lack a clear strategy for ending the conflict in Turkey’s southeast region. This not only hampers economic opportunities in the southeast, but will also undermine democratic governance in the years ahead. Moreover, throughout the review period, the government continued to repress dissent, for example, by openly threatening perceived opponents (e.g., activists, academics and journalists). Many journalists critical of the government now operate under financial threats, self-censorship and increased job insecurityThe influence of civil society organizations in decision-making processes remains limited. The massive polarization between pro- and anti-government camps is present across all spheres of political, economic and social life. The negative effects of this divide were evident in the aftermath of the parliamentary elections in June 2015, which failed to deliver a coalition government in line with the constitution, and in the April 2017 referendum on the introduction of the presidential system of government. This inability and/or unwillingness to engage in a power-sharing agreement demonstrates a serious crisis of democracy in Turkey. In the run-up to the June 2018 general elections, the AKP, and AKP Chairman and President Erdoğan secured a parliamentary majority by forming an informal alliance with the Nationalist Movement Party (MHP), which broke up in the second half of 2018. Over the last decade, Turkey has experienced important gains in income and living standards. Though economic competitiveness has decreased, recently. While economic growth returned after the 2016 economic slowdown, such positive signs are based on the availability of cheap and abundant credit, which increases demand (higher consumption and public expenditure) rather than efficiency. In late 2017 and for much of 2018, Turkey was shaken by a currency crisis in which the Turkish lira fell substantially against the U.S. dollar and the euro. Despite some effective counter-measures to rebalance the currency, the government refused to invite the International Monetary Fund to provide consultative support, and introduce substantial reforms to stabilize the monetary system and regain trust from international markets. Finally, environmental sustainability, energy security, sustainable urban development and progress toward a high-tech, science-based society are not assured in Turkey. Increased government spending (e.g., on research and development, education and vocational training, social policy, and health care) during the review period marked a step forward, but so far fails to show sustainable results.